Systemic immunity in herpetic keratitis. Issue 2 (February 1981) - Easty, D L; Carter, C; Funk, A
Abstract : The importance of specific immunity, especially cell-mediated, in resistance to herpes simplex disease is well documented, and animal experiments show that immune responses to previous herpetic infection can give considerable protection against reinfection in epithelial keratitis. Since susceptibility to stromal herpetic keratitis is probably determined in part by the extent of virus proliferation in the epithelium, immune responses to herpes simplex virus were studied in patients with epithelial or stromal keratitis, a group of patients with keratitis who were also severely atopic, and controls. The parameters measured were lymphocyte transformation, production of macrophage migration inhibition factor, and levels of serum antibody and immunoglobulin. No group differences were found except for a slight decrease in the whole blood culture assessment of lymphocyte transformation in stromal keratitis patients compared with seropositive controls and patients with epithelial disease. It is considered that in a small group of patients a deficiency in the specific cell-mediated immune response plays a role in determining the spread of virus into the corneal stroma.